Expanding the Iroquois genes repertoire: a non-transcriptional function in cell cycle progression - Barrios, Natalia (Fly (Austin), 2016)
Drosophila Iroquois (Iro) proteins are components of the TALE homeodomain family of transcriptional regulators. They play key roles in territorial specification and pattern formation. A recent study has disclosed a novel developmental function of the Iro proteins. In the eye and wing imaginal discs, they can regulate the size of the territories that they specify. They do so by cell–autonomously controlling cell cycle progression. Indeed, Iro proteins down-regulate the activity of the CyclinE/Cdk2 complex by a transcription-independent mechanism. This novel function is executed mainly through 2 evolutionarily conserved domains of the Iro proteins: the Cyclin Binding Domain and the IRO-box, which mediate their binding to CyclinE-containing protein complexes. Here we discuss the functional implications of the control of the cell cycle by Iro proteins for development and oncogenesis.